A cross-sectional study on knowledge, attitude, and practices of donning and doffing of personal protective equipment: an institutional survey on interns during the COVID-19 pandemic - Yendapu, Raja Sekhar; Yalamanchili, Vijay Krishna; Uthakalla, Vijaya Kumar; Naidana, Partha Sarathy; Kalapala, Abhilash; Abbavaram, Pavan Kumar (International Journal Of Community Medicine And Public Health, 2022)
Background: Personal protective equipment (PPE) is a physical barrier that healthcare workers (HCW) wear to stop the transmission of a pathogen from a pathologic specimen or a confirmed or suspected case. It prevents the spread of disease from patient to HCWs as well as the other way around. Eyewear, face shield, surgical mask, particulate respirators, glove, disposable gowns and boots, and head coverings are some examples of these physical barriers. The primary objective of the study is to assess the knowledge, attitude and practices (KAP) of interns towards appropriate use of PPE and secondary objective is to find the role of training on donning and doffing of PPE of interns towards appropriate use of PPE. Methods: This is an institutional based, analytical cross-sectional study. Data was collected from interns (n=130) posted in COVID-19 ward using a universal sampling method. A predesigned questionnaire was used for study. The data was analyzed using SPSS 26 trial version Results: Interns were aware of the importance and criticality of donning and doffing procedure, overall level of KAP of donning and doffing of PPE were 96.90%, 73.10% and 86.20% respectively. We found that there was statistically significant mean difference between the KAP scores with respect to training of PPE. Conclusions: There were some gaps in KAP at institutional level among the interns with regards to donning and doffing of PPE during the beginning of this pandemic.